Libraries and Climate Change: Pathways to Respond and Engage Communities - Reiman, Kara (Maine Policy Review, 2024)
As keystone community institutions, libraries are keenly aware of the increased interest in and heighted concerns about the impacts of climate change in their communities. This article examines how libraries are responding to these concerns, providing pathways for their patrons to engage in climate work, and stepping up to lead by example. The article focuses on work underway through a collaboration with the Gulf of Maine Research Institute and initiatives by libraries to make their footprint more sustainable. The article will provide stakeholders with insights into how to leverage and partner with the library community to address local, regional, and state climate priorities.